2020
DOI: 10.1007/s12325-020-01294-1
|View full text |Cite
|
Sign up to set email alerts
|

Service Evaluation of Methoxyflurane Versus Standard Care for Overall Management of Patients with Pain Due to Injury

Abstract: Introduction Inhaled methoxyflurane is an analgesic used for the emergency relief of moderate to severe pain in conscious adult patients with trauma and associated pain that is increasingly being used in hospital emergency departments to provide rapid analgesia. It is widely accepted that effective pain relief can facilitate patient care and flow through the emergency department (ED). The main aim of this evaluation was to assess the impact of inhaled methoxyflurane on patient length of stay (LOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Another study showed the overall cost of methoxyflurane use is 86 € (considering the staff costs and the cost of device). In general, the use of methoxyflurane will be a potential saving of 96 € for each patient with upper limb/shoulder injuries [54]. However, studies included in this meta-analysis did not present any pharmaco-economic related data.…”
Section: Discussionmentioning
confidence: 92%
“…Another study showed the overall cost of methoxyflurane use is 86 € (considering the staff costs and the cost of device). In general, the use of methoxyflurane will be a potential saving of 96 € for each patient with upper limb/shoulder injuries [54]. However, studies included in this meta-analysis did not present any pharmaco-economic related data.…”
Section: Discussionmentioning
confidence: 92%
“…Un estudio, que evaluó el uso de metoxiflurano inhalado versus sedación intravenosa para reducción de luxación anterior de hombro, demostró una disminución significativa de 50% para el grupo de metoxiflurano en la duración de la estancia en el Servicio de Urgencias. Otras ventajas encontradas fueron un menor uso de medicamentos intravenosos y la satisfacción final del paciente (12) .…”
Section: Servicio De Urgenciasunclassified
“…The use of inhaled methoxyflurane (IMF; Penthrox™, Galen Pharmaceuticals) has been well established in the acute trauma and emergency department (ED) setting [ 5 ]. It reduces the pain scores of trauma patients and decreases the patients’ length of stay in the ED [ 6 ]. In Australasia [ 7 , 8 ], the use of IMF is described in patients with pain associated with planned procedures rather than acute trauma, including change of burns dressings, incision and drainage of abscesses, and colonoscopies.…”
Section: Purposementioning
confidence: 99%